Artificial intelligence : methodology, systems, and applications : 17th International Conference, AIMSA 2016, Varna, Bulgaria, September 7-10, 2016, Proceedings /: methodology, systems, and applications : 17th International Conference, AIMSA 2016, Varna, Bulgaria, September 7-10, 2016, Proceedings. (2016) - Unknown
No abstract available